Memlük Sultanlarından Seyfeddin Ebûbekir ve Alaeddin Küçük Dönemlerinde (741-742/1341) Büyük Emirler Arasındaki Mücadeleler - Fatih Yahya Ayaz (Dini Araştırmalar, 2015)
After a period of stability and calm during the third sultanate of al-Malik al-Nasir Muhammad b. Qalawun (709-741/1310-1341), one of the most powerful sultans ofMamluks, Mamluk State entered a new turbulent time because of power struggle among the grand amirs who took the advantage of new sultans' being inexperienced and incapable. In this study, we dealt with this power struggle and its effects on the state